Studi Ma’āni Al-Hadist Terhadap Hadis-Hadis Keuntungan Jual Beli - Ahmad Hafid Safrudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Trade is a natural way to make a living to make ends meet, and everyone is free to try to obtain property and develop it. To obtain the coveted profit, there are many ways that sellers influence consumers to buy their wares. A possible way a manufacturer or seller is usually by selling a product much cheaper than the market price. For a while it may be that the seller did not make a profit, even the seller bought all these products with the intention that there was a vacancy of goods in the market, and as a result of which the consumer was very dependent on him. After the rival goes bankrupt, gradually the seller begins to dominate the market and monopolize it, so freely the seller will increase the price at an unreasonable price. The high selling price is due to the large demand. If a seller has mastered the market, the seller will make a price that generates more profit by increasing the price. The impact of intense business competition between merchants causes huge losses for consumers as the second party in buying and selling transactions by raising and lowering prices arbitrarily without thinking about the fate of consumers, especially from the lower middle economic community. Whereas basically, the need for primary/basic goods between one consumer and another is the same. Islam does not give certain restrictions on profits or profits in trade, this is left to each trader and the traditions of the surrounding community while maintaining the rules of justice and policies and prohibitions on giving madarat to oneself or to others.